Exploring self-regulation as a mediator between teaching method and students’ performance in Cambodian universities - Lork, Chumneanh; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
This study investigates the mediating role of self-regulation in the relationship between teaching methods and students’ academic performance in Cambodian higher education. The research aims to determine whether instructional strategies directly influence student outcomes and indirectly enhance performance by fostering self-regulation. A quantitative approach using SmartPLS (PLS-SEM) was applied to survey data from 320 academic staff across public and private universities. Measurement model results confirmed strong reliability and validity, while structural model analysis yielded R² values of 0.242 for self-regulation and 0.135 for students’ performance, indicating weak but acceptable explanatory power. Findings: Teaching methods had a significant positive effect on students’ performance (β = 0.183, t = 2.907, p = 0.004) and self-regulation (β = 0.491, t = 12.432, p = 0.000). Self-regulation positively influenced performance (β = 0.242, t = 3.867, p = 0.000) and partially mediated the relationship between teaching methods and performance (β = 0.119, t = 3.633, p = 0.000). The study highlights self-regulation as a critical mechanism linking teaching strategies to academic success. The findings suggest that higher education institutions should adopt learner-centered pedagogies and embed self-regulatory skill development into curricula to enhance student engagement and performance.